Successful treatment of relapsed chronic lymphocytic leukemia with venetoclax in a patient with severe chronic kidney disease. Issue 4 (14th April 2022) - Sugiura, Hiroyuki; Sezaki, Nobuo; Ishikawa, Tatsunori; Kuroi, Taiga; Okamoto, Sachiyo; Nomura, Naho; Masunari, Taro; Nakasako, Yukio; Kiguchi, Toru; Tanimoto, Mitsune
Abstract: Venetoclax is a promising new drug for relapsed or refractory chronic lymphocytic leukemia (CLL). However, venetoclax use had not been reported in severe chronic kidney disease (CKD) patients. We report the first case of relapsed CLL in a severe CKD patient that was successfully treated with venetoclax. Abstract : MR perfusion can be used to distinguish intracranial Rosai‐Dorfman disease from meningioma, and permit effective nonoperative treatment.